Juridical Review of Interfaith Marriage in Indonesia (Jessica Iskandar's Marriage to Ludwig Frans Willibald) - Tanuwijaya, Jessica; Syailendra Putra, Moody Rizqy; Santoso, Agnellya Hendarmin (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
In people's lives in Indonesia there are various problems related to the legitimacy of interfaith marriages because Indonesia has six recognized religions so it is not uncommon for people who want to marry of different religions. This study uses a normative legal research method using a statutory approach, judges' decisions, journals, books and research reports from the large Indonesian dictionary. The results of this study are that there are loose rules regarding the validity of interfaith marriages, starting from the side of religious law, national law and judges' considerations can determine the validity of interfaith marriages.